Preparing for the Second Surge: Preventing Posttraumatic Stress Disorder and Building Resilience for Health Care Workers in the Face of COVID-19 - Benham, Todd L. (Disaster Med Public Health Prep, 2020)
The global community needs to be aware of the potential psychosocial consequences that may be experienced by health care workers who are actively managing patients with coronavirus disease (COVID-19). These health care workers are at increased risk for experiencing mood and trauma-related disorders, including posttraumatic stress disorder (PTSD). In this concept article, strategies are recommended for individual health care workers and hospital leadership to aid in mitigating the risk of PTSD, as well as to build resilience in light of a potential second surge of COVID-19.